Herpetic Pneumonitis Following Posterior Fossa Surgery - Denis Ladouceur; Raymond Duperval; André Cantin; Eric H Frost (Canadian Journal of Infectious Diseases)
Reactivation of Herpes simplex virus (HSV) following manipulation of the trigeminal nerve root. has been reported in a substantial number of immunocompetent patients. Usually it was manifest as an oral mucocutaneous lesion and considered a benign postoperative complication. In the case described here, however, severe respiratory distress due to herpetic pneumonia developed following a pontocerebellar angle surgery complicated by an orolabial herpetic lesion. The delays necessary to confirm HSV diagnosis prior to initiating treatment are discussed, considering the rarity of this complication following neurosurgery.